Justification Logic as a foundation for certifying mobile computation - Bonelli, Eduardo (2012)
We explore an intuitionistic fragment of Artëmov's Justification Logic as a type system for a programming language for mobile units. Such units consist of both a code and a certificate component. Our language, the Certifying Mobile Calculus, caters for code and certificate development in a unified theory. In the same way that mobile code is constructed out of code components and extant type systems track local resource usage to ensure the mobile nature of these components, our system additionally ensures correct certificate construction out of certificate components. We present proofs of type safety and strong normalization for a run-time system based on an abstract machine.